2021
DOI: 10.1021/acsami.1c05944
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-Adjustable Metal–Organic Framework Nanorods for Efficient Oxygen Evolution Reaction

Abstract: A series of orientation-adjustable metal–organic framework (MOF) nanorods, CoFe­(dobpdc)-I to CoFe­(dobpdc)-III (dobpdc = 4,4′-dihydroxybiphenyl-3,3′-dicarboxylate), is developed on a 3D nickel foam (NF) template. By modulating the solvent composition for synthesis, the feature of MOF nanorods on the template can be varied from disorganized to a unidirectional orientation perpendicular to the NF. Well-aligned, vertically oriented CoFe­(dobpdc)-III nanorods are hydrophilic and have more exposed active sites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The Tafel slope of CP2 /GCE is also very low as compared to many other reported electrocatalysts. This is observed for only a few cases reported in the literature as shown in Table . For example, Wang et al reported the overpotential of 270 mV with a Tafel slope of 47 mV dec –1 in 0.1 M KOH at 10 mA cm –2 for a Fe/Ni-BTC MOF . Similarly, an overpotential of 93 mV but with a Tafel slope of 280 mV dec –1 in 0.1 M KOH at 10 mA cm –2 is reported for a Co-BTC MOF by Tripathy et al Therefore, low values of overpotential and Tafel slope are to be considered for an efficient electrocatalyst.…”
Section: Resultsmentioning
confidence: 91%
“…The Tafel slope of CP2 /GCE is also very low as compared to many other reported electrocatalysts. This is observed for only a few cases reported in the literature as shown in Table . For example, Wang et al reported the overpotential of 270 mV with a Tafel slope of 47 mV dec –1 in 0.1 M KOH at 10 mA cm –2 for a Fe/Ni-BTC MOF . Similarly, an overpotential of 93 mV but with a Tafel slope of 280 mV dec –1 in 0.1 M KOH at 10 mA cm –2 is reported for a Co-BTC MOF by Tripathy et al Therefore, low values of overpotential and Tafel slope are to be considered for an efficient electrocatalyst.…”
Section: Resultsmentioning
confidence: 91%
“…Ge prepared FeCo-MOF nanosheets and exhibited catalytic activity with the overpotential of 328 mV at 100 mA cm –2 in 1 M KOH for OER due to the synergistic effect between iron and cobalt ions. However, most bimetallic MFe-MOFs are mainly focused on NiFe-MOFs, , CoFe-MOFs, , or NiCoFe-MOFs, which exhibit excellent OER activity but poor HER activity. Recently, Liu synthesized Zn-doped CoP nanowall arrays and showed excellent HER activity, since the nonelectrochemically active Zn doping can produce more thermal neutral hydrogen adsorption free energy.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports of sunlight-driven photocatalysis of MoS 2 nanostructures such as nanoflowers, nanowires, and nanosheets. Solar power is one of the alternative, renewable energy sources to deal with the global energy crisis. As it is well-known, ultraviolet (UV), visible, and near-infrared (NIR) lighting accounts for about 5%, 45%, and 50% of the total energy of sunlight, respectively.…”
Section: Introductionmentioning
confidence: 99%